Investigations into the manzamine alkaloid biosynthetic hypothesis - Baldwin, J; Ciaridge, T; Culshaw, A; Heupel, F; Lee, V; Spring, DR; Whitehead, R; Boughtflower, R; Mutton, I; Upton, R (1998)
The biomimetic synthesis of a pentacyclic alkaloid (keramaphidin B, 1), an intermediate in the biogenetic pathway to the manzamine alkaloids, has been achieved. Compound 1 was formed by an intramolecular Diels-Alder reaction of macrocycle 2 in buffer followed by reduction with NaBH4. This reaction provides the first direct experimental evidence for the authors' biosynthetic hypothesis.